Development of an Instructional System Design Model as a Guideline for Lecturers in Creating a Course Using Blended Learning Approach - Chaeruman, Uwes Anis; Wibawa, Basuki; Syahrial, Zulfiati (International Journal of Interactive Mobile Technologies (iJIM), 2020)
Blended learning is not just merely blending face-to-face and online learning. The biggest challenge is making the right mix of relevant learning settings and teaching strategies to meet the learning outcomes. The latest study showed that research focusing on the instructional system design (ISD) model developments, especially related to blended learning approach, were still limited. This study aims to develop an ISD model that can provide a guideline for lecturers in creating a good course using a blended learning approach. This study applied a formative research method. A series of formative evaluation using several formative data collection techniques were used. They were expert review, one-to-one evaluations, and field tests. This study involved 242 respondents, consists of 7 instructional design and e-learning experts, and 235 lecturers. After conducted a series of formative evaluation stages, respondents able to create a good quality course using the ISD model developed.  Most of them get fair and low scores on the field test 1. The score increased significantly on the field test 2, where 33.6% get excellent scores, 48.2% get good scores, and 28.2% get fair scores. The score also increased significantly on field test 3 60.5% get excellent scores, 33.6% get good scores, and only 5.9% get poor scores. Hence, it can be concluded that the ISD model developed is feasible and usable. It can be used by higher education lecturers in Indonesia as a guideline in creating a course using blended learning approach.